Extra-Abdominal Fibromatosis (Desmoid Tumor): A Rare Tumor of the Lower Extremity Arising from the Popliteal Fossa - Mehmet Ali Kaygin; Ozgur Dag; Bilgehan Erkut; Azman Ates; Refik Cetin Kayaoglu; Hakan Kadioglu (Case Reports in Vascular Medicine)
Aggressive fibromatosis is a rare soft tissue tumor. Although it lacks metastatic potential, it can grow aggressively in a locally infiltrating pattern. The tumors frequently recur after surgical excision, which remains the treatment of choice. Optional combinations of radiotherapy and/or chemotherapy have been used postoperatively for recurrent disease and/or inoperable cases. A palpable mass was detected in the popliteal fossa of the right lower extremity in a 48-year-old man. Magnetic resonance imaging showed a contrast-enhancing noncalcified lesion initially felt to represent a vascular tumor. An invasive mass adherent to the surrounding tissue was visualized intraoperatively and extensively debulked. The patient's postoperative course was uneventful. Histologic examination of the surgical specimen was consistent with an extra-abdominal desmoid tumor. After appropriate recognition, wide local excision may be the most appropriate treatment for fibromatosis of the extremity. However, the rarity of this tumor and the difficulty inherent in distinguishing it from similar-appearing tumors are necessitating histologic confirmation of the diagnosis.